Change in non-abstinent WHO drinking risk levels and alcohol dependence: a 3 year follow-up study in the US general population. (June 2017) - Hasin, Deborah S; Wall, Melanie; Witkiewitz, Katie; Kranzler, Henry R; Falk, Daniel; Litten, Raye; Mann, Karl; O'Malley, Stephanie S; Scodes, Jennifer; Robinson, Rebecca L; Anton, Raymond; ,
Summary: Background: Alcohol dependence is often untreated. Although abstinence is often the aim of treatment, many drinkers prefer drinking reduction goals. Therefore, if supported by evidence of benefit, drinking reduction goals could broaden the appeal of treatment. Regulatory agencies are considering non-abstinent outcomes as efficacy indicators in clinical trials, including reduction in WHO drinking risk levels—very high, high, moderate, and low—defined in terms of mean ethanol consumption (in grams) per day. We aimed to study the relationship between reductions in WHO drinking risk levels and subsequent reduction in the risk of alcohol dependence. Methods: In this population-based cohort study, we included data from 22 005 drinkers who were interviewed in 2001–02 (Wave 1) and re-interviewed 3 years later (2004–05; Wave 2) in the US National Epidemiologic Survey on Alcohol and Related Conditions. Alcohol consumption (WHO drinking risk levels) and alcohol dependence (at least three of seven DSM-IV criteria in the previous 12 months) were assessed at both waves. We used logistic regression to test the relationship between change in WHO drinking risk levels between Waves 1 and 2, and alcohol dependence at Wave 2. Findings: At Wave 1, 2·5% (weighted proportion) of the respondents were very-high-risk drinkers, 2·5% were high-risk drinkers, 4·8% were moderate-risk drinkers, and most (90·2%) were low-risk drinkers. Reduction in WHO drinking risk level predicted significantly lower odds of alcohol dependence at Wave 2, particularly among very-high-risk drinkers (adjusted odds ratios 0·27 [95% CI 0·18–0·41] for reduction by one level, 0·17 [0·10–0·27] for two levels, and 0·07 [0·05–0·10] for three levels) and high-risk drinkers (0·64 [0·54–0·75] for one level and 0·12 [0·09–0·15] for two levels), and among those with alcohol dependence at Wave 1 (0·29 [0·15–0·57] for one level, 0·06 [0·04–0·10] for two levels, and 0·04 [0·03–0·06] for three levels in very-high-risk drinkers). Interpretation: Our results support the use of reductions in WHO drinking risk levels as an efficacy outcome in clinical trials. Because these risk levels can be readily translated into standard drink equivalents per day of different countries, the WHO risk levels could also be used internationally to guide treatment goals and clinical recommendations on drinking reduction. Funding: US National Institute on Alcohol Abuse and Alcoholism, New York State Psychiatric Institute, the Alcohol Clinical Trials Initiative.